2002
DOI: 10.1577/1548-8659(2002)131<0828:sbasfa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Striped Bass Annual Site Fidelity and Habitat Utilization in J. Strom Thurmond Reservoir, South Carolina-Georgia

Abstract: Forty-eight adult striped bass Morone saxatilis (3.2-19.1 kg) were captured by electrofishing in the tailrace of Richard B. Russell Dam and in the upper reaches of two major tributaries; they were implanted with temperature-sensitive radio transmitters and tracked approximately bimonthly for 20 months. As J. Strom Thurmond Reservoir downstream from the dam became thermally stratified in May, fish vacated the tributaries. From June to October, all striped bass were found within the reservoir's historical Savann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 23 publications
1
40
0
Order By: Relevance
“…However, the advent of radio, acoustic, archival and satellite tracking technology has provided researchers new avenues for examining the residency of target species within a specific habitat (e.g. Wilkerson and Fisher 1997;Meyer et al 2000;Block et al 2001;Boustany et al 2002;Young and Isley 2002;Sims et al 2003;Wetherbee et al 2003). More recently researchers have begun to use acoustic monitoring technology to simultaneously provide long-term data about the presence and movement patterns of groups of individuals within a population (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, the advent of radio, acoustic, archival and satellite tracking technology has provided researchers new avenues for examining the residency of target species within a specific habitat (e.g. Wilkerson and Fisher 1997;Meyer et al 2000;Block et al 2001;Boustany et al 2002;Young and Isley 2002;Sims et al 2003;Wetherbee et al 2003). More recently researchers have begun to use acoustic monitoring technology to simultaneously provide long-term data about the presence and movement patterns of groups of individuals within a population (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…During the habitat and seasonal-distribution portion of this telemetry study (Young and Isely 2002), we observed that striped bass were segregated by size during the summer months. Fish weighing more than 7 kg used different summering areas than those weighing less than 7 kg, and optimal habitat was found at the main summering areas of both size-classes.…”
Section: Discussionmentioning
confidence: 79%
“…Forty-eight harvestable striped bass (3.2-19.1 kg) were captured by electrofishing in J. Strom Thurmond Reservoir (Figure 1) and implanted with radio transmitters during May-June 1999 and March-June 2000. Radio transmitters were surgically implanted using standard techniques (see Young and Isely 2002 for details), and striped bass were released near the capture site.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, LMB are warm water species and tolerate higher temperatures and thus do not suffer as much from the temperature/dissolved oxygen (DO) "squeeze" characterized for cool-water striped bass (Coutant 1985, 1987, Zale et al 1990, Young and Isely 2002. Walleye have similar temperature and DO requirements as striped bass, with SMB temperature requirements intermediate between LMB and WAL (Fry 1947, Kitchell and Stewart 1977, MacClean et al 1981, Hurley 1986b, Buynak et al 1991.…”
mentioning
confidence: 99%